Does time heal all wounds? Restoring place attachment in Halifax's Point Pleasant Park after Hurricane Juan. (1st July 2019) - Larter, Patrick; Grek‐Martin, Jason; Silver, Amber
Abstract : On September 29, 2003, Hurricane Juan profoundly altered Halifax's Point Pleasant Park, resulting in feelings of solastalgia (the distress caused by perceived negative changes to a beloved place) as park users mourned the loss of a place that held great significance for the city. Starting in 2008, over 100, 000 trees have been planted in order to restore the original Acadian mixed forest to this landscape. Drawing on scholarly literature focused on place attachment and disaster recovery, this paper utilizes interviews (n = 11) and online surveys (n = 79) to determine whether long‐term park users have re‐established positive place attachments in conjunction with the park's restoration. Our results indicate that participants have largely overcome their solastalgic outlook and restored meaningful place attachments to the park. Unexpectedly, our results also suggest that long‐term participants have current place attachments that appear stronger than the place attachments expressed by participating short‐term users, who never experienced the traumatic impact of Hurricane Juan on Point Pleasant Park . Key Messages: Hurricane Juan's transformation of Point Pleasant Park disrupted established place attachments and generated overt feelings of solastalgia. Interview and survey results indicate that most participating long‐term users have restored meaningful place attachments to the park. Time does heal all wounds when paired with an effective restoration plan and users determined to reconnect to a cherished place. Est‐ce que le temps guérit toutes les blessures? Rétablir l'attachement au lieu dans le Parc Point Pleasant à Halifax après l'ouragan Juan: Le 29 septembre 2003, l'ouragan Juan a considérablement affecté le Parc Point Pleasant à Halifax, provoquant des sentiments de solastalgie (détresse causée par des changements environnementaux dans l'espace vécu). Ainsi, les usagers du parc ont subi la détérioration d'un endroit auquel la population d'Halifax attachait une grande importance. À compter de 2008, plus de 100 000 arbres ont été plantés afin de restaurer la forêt mixte acadienne originale et recréer les paysages associés. En nous inspirant des documents spécialisés mettant l'accent sur l'attachement au lieu et la réhabilitation après catastrophe, la présente étude utilise des entrevues (n = 11) et des sondages en ligne (n = 79) pour déterminer si les usagers à long terme du parc ont retrouvé un fort attachement au lieu à la suite de la restauration du parc. Nos résultats indiquent que les participants ont largement surmonté leur perspective solastalgique et qu'ils éprouvent à nouveau un attachement significatif au parc. Étonnamment, nos résultats suggèrent également que l'attachement actuel des utilisateurs à long terme semble plus fort que l'attachement au lieu exprimé par les usagers à court terme participant à l'étude, lesquels n'ont pas vécu l'impact traumatique de l'ouragan Juan sur le Parc Point Pleasant .